Incidental discovery of gastrointestinal stromal tumor via PSMA-PET/CT imaging: Insights from a case report - Venetia A. Florou; Diane K. Reyes; Kenneth J. Pienta (Urology Case Reports)
PSMA-PET/CT has emerged as a superior diagnostic tool for prostate cancer, demonstrating enhanced accuracy over conventional imaging methods. Although sensitive for detecting local and metastatic prostate tumors, it can also identify other non-prostate PSMA positive lesions. Here, we report a rare case of a 67-year-old patient with metastatic prostate adenocarcinoma who was found to have an incidental Gastrointestinal Stromal Tumor (GIST), during restaging with 68Ga-PSMA-11 PET/CT. Given the broad application of PSMA PET/CT in prostate cancer, its role in diagnosing other non-prostate PSMA tumors remains uncertain, highlighting the need for further research into its application in cancer management.